2019
DOI: 10.1016/j.jmst.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial bonding mechanism in Al/coated steel dissimilar refill friction stir spot welds

Abstract: Defect-free dissimilar Al/zinc coated steel and Al/AlSi coated steel welds were successfully fabricated by refill friction stir spot welding. However, Al alloy and uncoated steel could not be welded under the same welding condition. Al-Zn eutectic layer formed at the Al/zinc coated steel interface showed non-uniformity in thickness and nanoscale intermetallic (IMC) produced was discontinuous. The bonding formation between the Al-Zn layer and the surrounding materials was attributed to a liquid/solid reaction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…For FSpW welds of Al alloy to Zn-coated steel, a solid-liquid structure was produced, which was possibly induced by Zn melting and the dissolution of Mg-Al into Zn liquid [28]. Shen et al [29] fabricated FSpW welds of Al/Zn-coated steel and Al/AlSi-coated steel welds. Their results showed that Al-Zn eutectic layers with varied thickness were formed at the joint interface.…”
Section: Al/steel Dissimilar Alloy Weldmentioning
confidence: 99%
“…For FSpW welds of Al alloy to Zn-coated steel, a solid-liquid structure was produced, which was possibly induced by Zn melting and the dissolution of Mg-Al into Zn liquid [28]. Shen et al [29] fabricated FSpW welds of Al/Zn-coated steel and Al/AlSi-coated steel welds. Their results showed that Al-Zn eutectic layers with varied thickness were formed at the joint interface.…”
Section: Al/steel Dissimilar Alloy Weldmentioning
confidence: 99%
“…In particular, through the refill Friction Stir Spot Welding (refill FSSW) process, numerous solidification problems such as pores and cracks are avoided and high-quality joining of materials that are even considered as "unweldable" are enabled. The refill FSSW process was developed and patented by Helmholtz-Zentrum Geesthacht (HZG) [2,3] and many different material combinations in similar [4,5] and dissimilar joint configurations, such as Al/Mg [6,7], Al/steel [8,9] and Al/Ti [10,11], were already welded.…”
Section: Introductionmentioning
confidence: 99%
“…But zinc coating layer makes the surface characteristics of galvanized steel different from that of non-galvanized steel. These zinc coating layers are easy to damage in severe plastic deformation under external pressure and sliding friction [4][5][6]. It will also affect the formation of welding joints of stamping parts [7].…”
Section: Introductionmentioning
confidence: 99%